Membangun Kesadaran Kebersihan Dan Semangat Belajar Melalui Desain Poster Untuk MI Di Desa Sindon - Laura Zalfatika Azzahra; Shaneabel Azarya Utomo; Vincentius Alvin Resandy; Salahudin Al Ayubi Arya Wisanggeni; Yudi Wibowo; Arif Yulianto; Ahmad Khoirul Anwar (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
To build awareness of cleanliness and enthusiasm for learning through poster design for MadrasahIbtidaiyah (MI) in Sindon Village. This village was identified as facing challenges in increasing sanitation awareness and children's enthusiasm for learning. The service method involves preparing and installing posters specifically designed to communicate the message of cleanliness and enthusiasm for learning. The results of this activity show a significant increase in awareness of cleanliness, as can be seen from changes in children's behavior regarding personal hygiene and the surrounding environment. The creative and informative poster design succeeded in attracting children's attention, encouraging them to actively participate in maintaining cleanliness. The poster which included inspiration, motivational quotes and supporting visual images succeeded in providing positive encouragement to children's interest in learning. Students' active involvement in the learning process has increased, reflected in more active participation in class activities and increased learning outcomes. The use of poster design as an effective communication tool in this service has made a significant contribution to increasing awareness of cleanliness and enthusiasm for learning at MI 2 Sindon Village. It is hoped that this can be an inspiration for similar effortsin other communities to improve the quality of life and education of children through creative and participatory approaches.